Acetonitrile Coupling at an Electron‐Rich Iridium Center Supported by a PC sp 2P Pincer Ligand. Issue 22 (19th March 2013) - Burford, Richard J.; Piers, Warren E.; Parvez, Masood
Abstract: Aryl amido iridium complexes supported by a tridentate phosphanyl–carbene–phosphanyl pincer ligand [(PC   sp   2 P)Ir–N(H)Ar, Ar = C6 H5, 1a ; Ar = 2, 6‐ i Pr2 C6 H3, 1b ] react with acetonitrile to afford the dimeric complex2, in which two (PC   sp   2 P)Ir fragments are bridged by a diiminato ligand derived from two molecules of CH3 CN. Metrical parameters obtained from X‐ray structural determination of2 confirm that the bridging ligand is a diiminato species rather than an enediamido moiety, which indicates that the reductive coupling is mediated by one electron per iridium center. Experiments suggest that the reaction proceeds by heterolytic cleavage of the Ir–N(H)Ar bond followed by one‐electron reduction of the resulting Ir I –NCCH3 cation by the amido anion. The resulting anilino radical rapidly abstracts a hydrogen atom from the solvent. The reductive coupling of acetonitrile at a late transition metal center is unusual and in this instance occurs as a result of the highly σ‐donating, electron‐rich nature of the PC   sp   2 P ligand. Abstract : Electron‐rich Ir I aryl amido complexes undergo heterolytic bond cleavage and one‐electron reduction to effect coupling of a coordinated acetonitrile ligand. The dimeric product features a bridging diiminato ligand. The ability to mediate this coupling with a late transition metal attests to the highly donating nature of the PC   sp   2 P pincer ligand environment.